Emotion and imitation in early infant-parent interaction: a longitudinal and cross-cultural study - Kokkinaki, Theano (The University of Edinburgh, 1998)
Following a brief introduction to the diverse views on the motives for imitation, a review of the literature is presented covering the following topics: early theories and observations concerning the origin and development of human imitation in infancy; recent theoretical models that have emerged from experimental studies of infant imitation and from naturalistic studies of imitation in infant -mother communication; and traditional and recent theoretical and empirical approaches to imitative phenomena in infant -father interaction. This review leads to the following conclusions:

a) The failure of attempts to confirm certain ideas, hypotheses and suggestions built into the theories and strategies of earlier studies does not detract from their great contribution, which set the foundations upon which recent research is carried forward.

b) Despite the different theoretical frameworks and the lack of a consensus as to the best method for investigating early imitative phenomena in experimental settings, neonatal imitation is now accepted as a fact.

c) Imitative phenomena found in empirical studies focusing on infant -father interaction, as well as the relevant theoretical interpretations, are characterised by a contradiction; theory predicts bidirectional regulations, but studies employ an empirical approach that favours the view that regulation is only on the parental side.

In this investigation, observations were made of thirty infants, fifteen from Greece and fifteen from Scotland. All were seen every 15 days interacting with their mothers and with their fathers at home, from the 8th to the 24th week of life. A total of 540 home recordings were made. Units of interaction that contained imitative episodes were subjected to microanalysis with the aid of specialized software, in a multi -media system that provides the capability for detection, recording, timing and signal analysis of the variables under consideration to an accuracy of 1 /25th of a second.

The main findings may be summarised as follows: a) Imitation was evident, as early as the 8th week, irrespective of the country, the parent or the infant's sex. b) Cultural differences, reflecting the predominance of non -vocal and vocal imitative expressive behaviour in the two countries, were found. c) The developmental course of early imitative expressive behaviours was typically non -linear. d) Turn-taking imitative exchanges predominated over co-actions. e) Parents were found to imitate their infants more than vice versa. f) Regulation of emotion, either in the sense of emotional matching or of emotional attunement, proved to be the underlying motivating principle for both parental and infant imitations.

The implications of these findings for understanding universal intersubjective nature of early imitation in infant -father and infant-mother interactions are discussed.